Experimental Measurements of a Model of Pile, Slab and Raft Foundation - Burkovič Kamil; Buchta Vojtěch (Transactions of the VŠB: Technical University of Ostrava, Civil Engineering Series, 2014)
A design of the load-bearing capacity and settlement of a pilot base is usually based on the assumption that all of the load from the top of the building is transferred only by pilots. The influence of the adjacent connecting structures, which are in contact with the ground (pile cap, slab, block, belt, etc.), is usually ignored. The necessary data from the experimental measurement of the impact of these structures, concerning the overall bearing capacity of the foundations, was obtained on the testload device (Stand), in the area of Faculty of Civil Engineering, VŠB-TU of Ostrava. The progress of the experiment and the results of the load tests are listed in this paper